Visual-Kinesthetic Strategies to Increase Sitting Duration in Early Childhood: Strategi Visual-Kinestetik Meningkatkan Durasi Duduk Anak Usia Dini - Cahyaningrum, Sekar Alphiani; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Sidoarjo, 2025)
Sitting endurance in early childhood is a critical aspect of successful classroom learning, particularly as children transition into more structured educational environments. Previous studies have noted that many early learners struggle to remain seated for developmentally appropriate durations, hindering their ability to engage effectively in learning activities. However, limited empirical research has addressed instructional strategies tailored to improve sitting endurance in PAUD (Pendidikan Anak Usia Dini) students. This study aims to investigate the role of the Picture and Picture method, a visually driven and kinesthetic teaching approach, in supporting sitting endurance among early childhood learners. Utilizing a single-subject quantitative quasi-experimental design with an A-B-A framework and interrupted time series, one five-year-old male student was observed under three conditions: pre-intervention, during intervention, and post-intervention. Visual data analysis showed an increase in sitting duration from 7–10 minutes during the baseline to 20–25 minutes post-treatment. The novelty of this study lies in applying the Picture and Picture method not only for cognitive outcomes but also for behavioral endurance. These findings imply that integrating visual-kinesthetic strategies may support behavioral readiness in early learners, offering practical guidance for PAUD educators seeking to prepare children for structured learning environments. Highlight: Supports sitting behavior through visual-kinesthetic learning. Uses single-subject A-B-A experimental design. Offers practical insights for PAUD instructional methods Keyword: Sitting Endurance, Early Childhood Education, Picture and Picture, Visual Learning, Classroom Behavior